Fetal gender, serum human chorionic gonadotropin, and testosterone in women with preeclampsia - Zakia M. Ibrahim; Eman A. Kishk; Mahmoud S. Elzamlout; Amal M. Elshahat; Omima T. Taha (Taylor & Francis Group, 2020)
Objectives Evaluation of the association between fetal gender, serum beta-human chorionic gonadotropin, and serum testosterone, and preeclampsia. Methods Case-control study conducted at the Obstetrics and Gynecology Department. 120 patients divided into study group (patients with preeclampsia subdivided into mild and severe) and control group (normotensive women). Interventions Fetal gender was determined. Serum testosterone and HCG levels were estimated at 32 weeks or at the time of diagnosis of preeclampsia (study group) or recruitment (control group). Results Positive association between the male gender of the fetus and preeclampsia. Increased HCG and Testosterone were associated with developing preeclampsia. Conclusion The mechanism of preeclampsia could be androgen-mediated. There is a significant correlation between serum HCG and testosterone and preeclampsia.